2022
DOI: 10.3389/fimmu.2022.888278
|View full text |Cite
|
Sign up to set email alerts
|

T and B Cell Composition and Cytokine Producing Capacity Before and After Bariatric Surgery

Abstract: Morbid obesity is associated with a chronic state of low-grade inflammation, which may lead to accelerated differentiation of T and B cells. These differentiated immune cells are strongly cytotoxic and have an increased pro-inflammatory cytokine producing capacity. Furthermore, the anti-inflammatory function of the T and B cells decreases. The aim of this study was to evaluate the effect of morbid obesity on the subset profile and cytokine producing capacity of T and B cells. Subsequently, we assessed whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 53 publications
4
19
1
Order By: Relevance
“…This strategy enabled us to identify the following populations within the CD19 + B cell compartment: IgD + CD27 − naïve, IgD − CD27 + class-switched and IgD + CD27 + unswitched memory, IgD − CD27 − DN cells, CD24 hi CD38 hi transitional, CD24 int CD38 int mature, CD24 hi CD38 lo total memory, CD24 lo CD38 lo activated B cells, and CD24 int CD38 hi pre-plasmablasts. As reported previously (12,22), we found a signi cant expansion of IgD + CD27 − naïve B cells in individuals with obesity compared to lean controls, which was normalised to control levels following surgery (Fig. 1a).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…This strategy enabled us to identify the following populations within the CD19 + B cell compartment: IgD + CD27 − naïve, IgD − CD27 + class-switched and IgD + CD27 + unswitched memory, IgD − CD27 − DN cells, CD24 hi CD38 hi transitional, CD24 int CD38 int mature, CD24 hi CD38 lo total memory, CD24 lo CD38 lo activated B cells, and CD24 int CD38 hi pre-plasmablasts. As reported previously (12,22), we found a signi cant expansion of IgD + CD27 − naïve B cells in individuals with obesity compared to lean controls, which was normalised to control levels following surgery (Fig. 1a).…”
Section: Resultssupporting
confidence: 85%
“…Bariatric surgery, indicated as an intervention for obesity (6), is associated with signi cant and sustained weight loss, as well as improved metabolic health and reduction in circulating in ammatory factors long-term (7)(8)(9)(10)(11). More recent studies have started to address the impact of bariatric surgery on immune compartments (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these imbalances can have an impact on tumor and immune cells. For instance, T cell proliferation and counts are decreased, and the T cell subset composition is altered in obese as compared to lean individuals in non-cancer-related settings [ 22 , 23 , 24 , 25 , 26 ]. For instance, Wijingaarden et al reported a shift from naïve T cells and effector memory cells re-expressing CD45RA T cells (T EMRA ) towards a higher proportion of central-memory T cells (T CM ) for CD4 + Tells in morbidly obese patients compared to lean controls.…”
Section: Sources Of Lipids Within the Tumor Microenvironmentmentioning
confidence: 99%
“…Contrarily, these patients also showed a higher proportion of CD8 + naïve T cells, effector memory T cells (T EM ) and T EMRA as well as a decreased T CM compartment. Of note, cytokine production of IL-2 and IFN-γ was decreased in CD8 + but not CD4 + T cells in those patients compared to lean controls [ 26 ]. Obesity affects T cell formation already in the thymus, resulting in accelerated thymic aging and a limited T cell repertoire [ 27 ].…”
Section: Sources Of Lipids Within the Tumor Microenvironmentmentioning
confidence: 99%